2002
DOI: 10.1046/j.1460-9568.2002.02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Neither ibotenic acid nor volkensin lesions of the nucleus accumbens shell affect the expression of cocaine sensitization

Abstract: Studies have shown that the nucleus accumbens shell plays an integral role in the expression of psychostimulant-induced behavioural sensitization. Dopaminergic regulation of excitatory amino acid inputs in this region of the brain could be a key factor in the neural influence of this phenomenon. Alterations in the dopaminergic innervation patterns in the shell have been demonstrated in rats that received repeated cocaine injections. Furthermore, lesions of brain regions that send projections to the shell alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…It should be emphasized that our experiments were designed to test the hypothesis that enhanced AMPAR surface expression is required for the expression of locomotor sensitization, not to determine if there is an absolute requirement for some level of AMPAR transmission. Finally, it is important to note that our CNQX infusions into the NAc core do not address the role of AMPAR transmission in the NAc shell in the expression of sensitization (but see Todtenkopf et al, 2002) or the role of AMPAR transmission in the DS.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that our experiments were designed to test the hypothesis that enhanced AMPAR surface expression is required for the expression of locomotor sensitization, not to determine if there is an absolute requirement for some level of AMPAR transmission. Finally, it is important to note that our CNQX infusions into the NAc core do not address the role of AMPAR transmission in the NAc shell in the expression of sensitization (but see Todtenkopf et al, 2002) or the role of AMPAR transmission in the DS.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, psychostimulant sensitization-induced long-term changes in cellular reactivity or cellular morphology are not generally found in the nucleus accumbens shell after psychostimulant administration (Cadoni et al 2000 ; Li et al 2004 ; Todtenkopf et al 2002a ). Moreover, post induction lesions of the shell leave the expression of cocaine sensitization intact (Todtenkopf et al 2002b ), although preinduction lesions of a subarea of the shell result in reduced sensitized, but not acute responses to cocaine (Brenhouse and Stellar 2006 ). On the other hand, microinjection of amphetamine or cocaine into the shell (but not core) produces sensitized psychomotor responses and augmented dopamine levels in animals pretreated with cocaine (Filip and Siwanowicz 2001 ; Pierce and Kalivas 1995 ), and sensitized cellular reactivity has been observed in specific subareas within the accumbens shell after repeated cocaine administration (Brenhouse et al 2006 ; Todtenkopf et al 2002a ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of sensitization of c- fos expression in the medial prefrontal cortex corresponds well with results from other groups showing similar results after 2 weeks of abstinence (Todtenkopf et al 2002a ). Sensitization of c- fos immunoreactivity does occur when animals are challenged after 2 days of abstinence (Hedou et al 2002 ; Todtenkopf et al 2002a , b ), suggesting a role in the induction or early phases of sensitization. In support of a role for the prefrontal cortex in the induction and early phases of expression, lesion studies have demonstrated region-specific effects in the involvement of prefrontal areas in the induction of cocaine sensitization (Tzschentke and Schmidt 2000 ), and lesions of the entire medial prefrontal cortex have been shown to prevent the induction of amphetamine sensitization (Wolf et al 1995 ; Cador et al 1999 , but see Tzschentke and Schmidt 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…CNQX is a competitive antagonist, so its efficacy might be influenced by procedural differences that alter the level of cocaine-induced glutamate release in the NAc. Other differences between the studies (e.g., withdrawal time) may also contribute to the discrepancy (see Ferrario et al, 2010 for more discussion) and it is notable that none of the CNQX studies targeted the shell (but see Todtenkopf et al, 2002). Nevertheless, given that CNQX certainly produced some reduction of AMPAR occupancy, our results suggest that one can reduce AMPAR occupancy in the core without affecting the magnitude of the sensitized locomotor response.…”
Section: Ampar Adaptations Accompanying Sensitization To Cocainementioning
confidence: 99%